The Jewishness of Jesus and Christian-Jewish Dialogue: A Colloquium in Honor of Joep van Beeck, S.J. - Tobin, S.J., Thomas H.; Mallow, Jeffry V. (Studies in Christian-Jewish Relations, 2011)
No abstract is available.